The Mid-Life Dip in Well-Being: A Critique - David G. Blanchflower; Carol L. Graham (Global Labor Organization (GLO), 2021)
A number of studies - including our own - find a mid-life dip in well-being. Yet several papers in the psychology literature claim that the evidence of a U-shape is "overblown" and if there is such a thing that any such decline is "trivial". Others have claimed that the evidence of a U-shape "is not as robust and generalizable as is often assumed," or simply "wrong." We identify 424 studies, mostly published in peer reviewed journals that find U-shapes that these researchers apparently were unaware of. We use data for Europe from the Eurobarometer Surveys (EB), 1980-2019; the Gallup World Poll (GWP), 2005-2019 and the UK's Annual Population Survey, 2016-2019 and the Census Bureau's Household Pulse Survey of August 2021, to examine U-shapes in age in well-being. We find remarkably strong and consistent evidence across countries of statistically significant and non-trivial U-shapes in age with and without socio-economic controls. We show that studies cited by psychologists claiming there are no U-shapes are in error; we reexamine their data and find differently. The effects of the mid-life dip we find are comparable to major life events such as losing a spouse or becoming unemployed. This decline is comparable to half of the unprecedented fall in well-being observed in the UK in 2020 and 2021, during the Covid19 pandemic and lockdown, which is hardly "inconsequential" as claimed.
Keywords: 330